EGFR/HER-targeted therapeutics in ovarian cancer. (March 2012) - Wilken, Jason A; Badri, Tayf; Cross, Sarah; Raji, Rhoda; Santin, Alessandro D; Schwartz, Peter; Branscum, Adam J; Baron, Andre T; Sakhitab, Adam I; Maihle, Nita J
Despite decades of research and evolving treatment modalities, survival among patients with epithelial ovarian cancer has improved only incrementally. During this same period, the development of biologically targeted therapeutics has improved survival for patients with diverse malignancies. Many of these new drugs target the human epidermal growth factor receptor (EGFR/HER/ErbB) family of tyrosine kinases, which play a major role in the etiology and progression of many carcinomas, including epithelial ovarian cancer. While several HER-targeted therapeutics are US FDA approved for the treatment of various malignancies, none have gained approval for the treatment of ovarian cancer. Here, we review the published literature on HER-targeted therapeutics for the treatment of ovarian cancer, including novel HER-targeted therapeutics in various stages of clinical development, as well as the challenges that have limited the use of these inhibitors in clinical settings.